2015
DOI: 10.3960/jslrt.55.145
|View full text |Cite
|
Sign up to set email alerts
|

TET2 Mutation in Adult T-Cell Leukemia/Lymphoma

Abstract: Loss-of-function of ten-eleven translocation-2 (TET2) is a common event in myeloid malignancies, and plays pleiotropic roles, including augmenting stem cell self-renewal and skewing hematopoietic cells to the myeloid lineage. TET2 mutation has also been reported in lymphoid malignancies; 5.7∼12% of diffuse large B-cell lymphomas and 18∼83% of angioimmunoblastic T-cell lymphomas had TET2 mutations. We investigated TET2 mutations in 22 adult T-cell leukemia/lymphoma (ATLL) patients and identified a missense muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Recent studies have reported the presence of TET2 mutations in ATLL patients from Japan [ 21 23 ]. However, whether TET2 mutations also exist in ATLL patients from other origins and whether they are specific for a clinical subtype of ATLL have not been investigated yet.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have reported the presence of TET2 mutations in ATLL patients from Japan [ 21 23 ]. However, whether TET2 mutations also exist in ATLL patients from other origins and whether they are specific for a clinical subtype of ATLL have not been investigated yet.…”
Section: Resultsmentioning
confidence: 99%
“…A simple explanation could be that reduced 5-hmc is due to TET2 mutations. Indeed, recent studies reported TET2 somatic mutations in ATLL patients from Japan (∼10% of patients) [ 21 23 ]. Our present data show on the one hand that TET2 mutations also exist in ATLL patients from African origin and on the other hand, that they are especially detected in the aggressive subtype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the accumulation of reactive oxygen species (ROS) results in DSBs in DNA . In addition, tax hinders DNA double‐strand break (DSB) repair factors and causes structural genomic abnormalities and aneuploidy . Tax disrupts SAC through the impact on the human homolog of MAD1, a vital component of the spindle checkpoint, which proceeds mitosis even though the correct attachment of sister chromatids to the mitotic spindle is impaired.…”
Section: Oncogenic Viruses and Their Role In Causing Aneuploidymentioning
confidence: 99%
“…Of these, TET2 was most frequently mutated in angioimmunoblastic T-cell lymphomas (up to 76%) and "Th follicular (TFH)−like" peripheral T-cell lymphomas (PTCL), not otherwise specified [10][11][12] (19-51%). TET2 mutation was also observed in approximately 10% of adult T cell leukemia/lymphoma cases 13,14 . As for B-cell malignancies, 0-12% of DLBCL patients were reported to carry TET2 mutation [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%